Perbaikan Klinis Green Nail Syndrome yang Signifikan pada Lanjut Usia dengan Terapi Kombinasi: Sebuah Serial Kasus - Marizki Ramadhani, Reinanda; Nadia Yusharyahya, Shannaz; Legiawati, Lili; Astriningrum, Rinadewi; Gunardi, Keiko Yolanda; Reshinta, Reisa (Jurnal Kedokteran Meditek, 2025)
Introduction: Green nail syndrome is a common bacterial infection of the nails and is characterized by green discolouration of the nail plate caused by Pseudomonas aeruginosa. It frequently occurs in people who are exposed to constant water and due to mechanical trauma, especially in elderly patients. Case Illustration: We reported 2 cases treated with a combination therapy of oral ciprofloxacin, 1% acetic acid dressing, gentamicin ointment and showed a significant clinical improvement. There are two cases: a 67-year-old man and a 64-year-old woman complained of black-greenish discolouration on his right big toenail, which has been accompanied by changes in the shape of the nail for 3 months. Both patients have a history of frequent and prolonged contact with water—dermoscopy results in greenish-black discolouration in the nail plate.  The culture results of both patients, Pseudomonas aeruginosa was found. Combination treatment showed significant clinical improvement in both patients. Discussion: Dressing of 1% acetic acid was useful as an adjuvant to improve the ointment penetration, inhibiting the formation of Pseudomonas aeruginosa biofilms. Gentamicin and ciprofloxacin are effective against aerobic gram-negative bacterial infections, such as Pseudomonas aeruginosa. Conclusion: The use of ciprofloxacin is recommended, especially in elderly patients. Combination therapy with oral ciprofloxacin, 1% acetic acid dressing, and gentamicin ointment is an effective option for patients with green nail syndrome